Pengaruh Penerapan PSAK 71 terhadap Pencatatan, Pengakuan, Pengukuran dan Penyajian Cadangan Penurunan Nilai Piutang pada PT. Pelabuhan Indonesia (Persero) Regional 1 Cabang Belawan - Devi Irma Yunita; Rini Indahwati (Indonesian Accounting Research Journal, 2022)
Impairment has been an interesting issue since PSAK 71 came into effect. The existence of significant differences with the previous standard (PSAK 55) causes companies to need to review and adjust in order to create better financial reporting. This final report aims to analyze the application of PSAK 71 in the calculation of allowance for impairment of receivables at PT. Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch and see the suitability of the application of PSAK 71with generally accepted accounting standards. This research concludes that PT. Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch has performed accounting treatment for trade receivables and impairment of trade receivables in accordance with PSAK 71 and generally accepted accounting principles. The increase in allowance for impairment of value by 219.60% was due to the transition from PSAK 55 to PSAK 71